124 Value of Myocardial Perfusion Imaging (MPI) in Preoperative Renal Transplant Assessment. Experience of the University Hospital of Wales. (31st May 2014) - Budzbon, Dominika; Edwards, Heather; Wheeler, Richard; Griffin, Sian; Inam, Wajiha; Lau, Yee C
Abstract : Introduction: Although national guidance does not recommend screening of coronary artery disease in asymptomatic patients with established renal failure, cardiovascular disease is a leading cause of death in patients on dialysis and transplant recipients.Therefore "Cardiac assessment pathway" was developed in the UHW, Cardiff, for renal transplant candidates, to assess fitness for surgery in patients mainly of intermediate to high cardiovascular risk, even if asymptomatic from cardiovascular perspective, and to identify high risk patients who require targeted investigation and revascularisation prior to renal transplant. Method: Audit included data of 104 patients referred for cardiac assessment with MPI for suitability for renal transplant between April 2011 and October 2013. Data obtained from risk assessments questionnaires, MPI, Echo, angiogram and perioperative transplant notes.MPI results categorised as: normal, reversible ischaemia, fixed defect, mixed defect and inconclusive.104 MPI performed in 25% females, 75%, males age 33–79, initial cardiovascular risk categorised as low (9.7%), intermediate (42.3%) or high (48%). Adenosine used in 79%, exercise in 16%, dobutamine in 4% of patients. Results: 51% of MPI results were normal (SSS 0–5, average 0.3), 13.5% revealed reversible ischaemia (SSS 3–11, average 5.9), 24% showed fixed (SSS 0–16, average 2.8) and 11.5% (SSS 5–18, average 9.6) mixed defect. 11/56 (20%) of asymptomatic patients were referred for coronary angiogram following MPI (coronary artery disease confirmed in 4, all for medical management, 7 patients awaiting angiogram). In 50% of low risk patients MPI was normal, 40% had a fixed defect and 10% had small reversible ischaemia, all deemed fit for surgery, 3 have had a transplant with uneventful perioperative period. 61% of MPI in an intermediate risk group were normal, 18% showed fixed, 9% mixeddefect and 11% showed reversible ischaemia, out of which 1(20%) subsequently underwent PCI, 1 was referred for medical management and further 5 are awaiting angiogram. 9 patients (deemed fit for surgery following MPI) have already had a transplant with no cardiac events perioperatively. 22 patients (44%) in the high risk group had a normal scan and were deemed fit for surgery, 1 deemed not fit for transplant following MPI. 8 out of remaining 28 patients were referred for angiogram, 5 subsequently referred for medical management and deemed fit for transplant. 16 had a transplant with 1cardiacevent perioperatively.Overall 83/104 (80%) were deemed fit for surgery following MPI, 1 turned down from surgery, 16 referred for further coronary assessment, 5 for MDT discussion. Conclusion: MPI is a valuable tool in cardiovascular risk stratification of renal transplant candidates and identifies high risk patients for further coronary investigations and intervention prior to them being considered for renal transplantation.